2014
DOI: 10.1021/jp501611t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silicon Doping on the Reactivity and Catalytic Activity of Gold Clusters

Abstract: Doping is known to be an excellent and simple way of catalyst design. Although notable progress has been made in understanding the reactivity and catalytic activity of gas-phase and supported gold clusters, very few studies have been carried out on the doped gold clusters. In the present work, we have carried out density functional theory calculations to investigate the effect of silicon doping on the reactivity and catalytic activity of gold nanoclusters. The present work particularly focuses on the adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 65 publications
2
34
0
Order By: Relevance
“…We used the Modified LANL2DZ basis set by Hay and Wadt that replaces the 60 core electrons of Au atoms by an effective core potential (ECP) obtained from calculations which incorporate relativistic corrections, and contracted Gaussian basis functions for the remaining 19 valence electrons (5s 2 5p 6 5d 10 6s 1 ). This basis set has been widely used in a number of articles for studying properties of gold clusters . Three gold atoms have 57 valence electrons, and a preliminary CAS(7,4) calculation, using Cs symmetry, including the HOMO/LUMO of each symmetry resulted in a 2 E neutral cluster and 1 A 1 cation cluster (labels in C 3 v ).…”
Section: Resultsmentioning
confidence: 99%
“…We used the Modified LANL2DZ basis set by Hay and Wadt that replaces the 60 core electrons of Au atoms by an effective core potential (ECP) obtained from calculations which incorporate relativistic corrections, and contracted Gaussian basis functions for the remaining 19 valence electrons (5s 2 5p 6 5d 10 6s 1 ). This basis set has been widely used in a number of articles for studying properties of gold clusters . Three gold atoms have 57 valence electrons, and a preliminary CAS(7,4) calculation, using Cs symmetry, including the HOMO/LUMO of each symmetry resulted in a 2 E neutral cluster and 1 A 1 cation cluster (labels in C 3 v ).…”
Section: Resultsmentioning
confidence: 99%
“…They observed that the neutral Au 6 cluster is stable up to 1100 K, whereas the cationic and the anionic clusters are stable up to 500 K. On ligating the cluster with CO, the neutral and anionic conformations are stable up to 800 K whereas the cationic cluster collapses at room temperature. In a recent work by Manzoor et al on silicon‐doped gold clusters, they have observed preferential binding and activation of the O 2 molecule in Au 7 Si in comparison to Au 8 cluster. Further the Au 7 Si cluster exhibited enhanced catalytic activity for CO oxidation.…”
Section: Introductionmentioning
confidence: 97%
“…We note that the significance of the concerned reactions is well‐known in the scientific literature and each of these reactions presents some unique challenges. CO oxidation reaction has important implications on the environment and to this end, Au based metal clusters are considered to be among the best performing catalytic agents . CF bond decomposition from alkyl/aryl halides could be a very useful pathway toward CC bond formation processes and as a result CF bond activation represents an interesting research topic .…”
Section: Introductionmentioning
confidence: 99%